Preferensi Konsumen Terhadap Produk Olahan Cabai Berupa Sambal Instan di Kecamatan Andir Kota Bandung - Natania, Raden Agrinda Regita; Rachmawati, Erna; Suminartika, Eti; Renaldi, Eddy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Processed chili products are the choice of the people of Bandung City, supported by a lifestyle that wants everything to be practical, instant, and easy to use, without having to take a long time. One of the processed chilies that has been developed at this time is instant sambal products. In consuming a product, consumers will pay attention to the quality of the product to be consumed, this is also called consumer preference. This research aims to determine consumer preferences for the attributes of price, taste, packaging, and variations of instant sambal and to determine the order of instant sambal attributes based on the level of importance according to consumer preferences in Andir District, Bandung City. The use of quantitative descriptive methods with survey techniques in the form of questionnaires was distributed to 120 respondents in Andir District, Bandung City. The data analysis technique is conjoint analysis. The research results showed that the combination of product attributes that respondents liked most was instant sambal with variations of shrimp paste-based sambal, price less than IDR 30,000, size > 250 gr (large size), jar packaging, with a medium spicy taste and an attribute importance level of the highest value to the lowest in the variation attribute, the price attribute, the size attribute, the taste attribute, and finally the packaging attribute.